Pemetaan Partisipatif Infrastruktur Air Bersih Berbasis Sistem Informasi Geografis untuk Penguatan Tata Kelola Air Bersih di Negeri Mamala Kabupaten Maluku Tengah - Wa Ode Sitti Jurianti Aswad; Hertine Megiestri Kesaulya; Resky Prafitri (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The availability of spatial data on clean water infrastructure that is not yet integrated in the Negeri Mamala makes it difficult for the state government to monitor networks, determine repair priorities, and plan the development of clean water services. This community service activity aims to produce a Geographic Information System (GIS)-based map of clean water infrastructure, identify the existing conditions of the infrastructure, and enhance the capacity of state officials in utilizing spatial data. The activity involves Negeri Mamala and local communities as participants in the mapping and data validation process. The implementation methods include initial coordination, field surveys, GPS mapping, technical observations, participatory interviews, data processing using ArcGIS 10.8, joint validation with partners, and guidance on map utilization. Data analysis was conducted in a descriptive-spatial manner to identify infrastructure conditions, location distribution, and connectivity of the clean water network. The results of the activities showed that 13 infrastructure points were successfully mapped, including water sources, storage tanks, drilled wells, dug wells, service points, and distribution pipe networks. The outputs of the activities include digital maps, printed maps, and technical infrastructure notes. This GIS-based participatory mapping can support planning, network evaluation, and the strengthening of clean water governance in Negeri Mamala. This activity is still limited to mapping the existing conditions of clean water infrastructure. Therefore, further data development and analysis are needed to support more sustainable service planning